Analisis Pentingnya Penambahan Fitur Informasi Ruang Inap Pada Aplikasi Halodoc: Perspektif Pengguna Di Kecamatan Balongbendo - Herninda Dara Puspita Ayu; Rusdi Hidayat Nugroho (Jurnal Pengabdian Masyarakat, 2023)
M-health is a mobile technology that makes it easier to access health services. One of the most popular M-health in Indonesia, namely Haldoc, which offers health services. One of the crucial feature developments is the inpatient room availability information feature. This study uses Balongbendo District as the object of research, because with a significant population, people still experience limitations in accessing health services in the area. So this research objective is to analyze the importance of adding inpatient information features to the Halodoc application, with the perspective of users in Balongbendo District. This study uses survey methods and user interviews in the Balongbendo District area with an age range of 21-35 years. Data analysis was carried out through a qualitative approach. The results of the study show that the addition of an inpatient information feature to Halodoc generates interest and provides benefits for users in Balongbendo District. This feature also helps optimize time in obtaining access to health services and seeking information about inpatient rooms, as well as providing certainty and trust.